2012
DOI: 10.1039/c2cc35392j
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive functionalization of polymers of intrinsic microporosity for enhanced CO2 capture

Abstract: Modifying sorbents for the purpose of improving carbon dioxide capture often results in the loss of surface area or accessible pores, or both. We report the first noninvasive functionalization of the polymers of intrinsic microporosity (PIMs) where inclusion of the amidoxime functionality in PIM-1 increases carbon dioxide capacity up to 17% and micropore surface area by 20% without losing its film forming ability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
203
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(220 citation statements)
references
References 33 publications
16
203
1
Order By: Relevance
“…Zulfiqar et al recently reported one of the few studies of amidoxime, presenting both theoretical and experimental work that demonstrated the potential of amidoxime for CO 2 separation [17]. Patel modified polymers of intrinsic microporosity with amidoxime and observed an increase in CO 2 adsorption capacity [18]. In our work, we grafted the amidoxime group onto the surface of porous carbon synthesized by a soft-templating method and measured CO 2 adsorption parameters.…”
Section: Introductionmentioning
confidence: 88%
“…Zulfiqar et al recently reported one of the few studies of amidoxime, presenting both theoretical and experimental work that demonstrated the potential of amidoxime for CO 2 separation [17]. Patel modified polymers of intrinsic microporosity with amidoxime and observed an increase in CO 2 adsorption capacity [18]. In our work, we grafted the amidoxime group onto the surface of porous carbon synthesized by a soft-templating method and measured CO 2 adsorption parameters.…”
Section: Introductionmentioning
confidence: 88%
“…Modifications to the nitrile substituents of PIM-1 to introduce carboxylic acid, thioamide, and tetrazole groups all significantly reduce the apparent surface area presumably due to the hydrogen bonding properties of these groups increasing polymer cohesion and improving packing [69,71,73]. However, the introduction of amidoxime substituents does not reduce significantly the apparent surface area and has thus been termed a "non-invasive" modification [72].…”
Section: Microporositymentioning
confidence: 99%
“…These include simple hydrolysis groups to provide carboxylic acids [69,70], reaction with P 2 S 5 to provide thioamines [71], reaction of hydroxylamine to give amidoximes [72], and the reaction of sodium nitride to provide tetrazole functionality (Scheme 2) [73].…”
Section: Synthesis Of Pimsmentioning
confidence: 99%
“…Amidoximes are known to be CO 2 -philic [114], and functionalization of PIM-1 by amidoxime will create sites that have strong affinity toward CO 2 through its high quadruple moment. In 2012, Patel and Yavuz [115] synthesized the amidoxime-PIM-1 successfully through a conventional and non-invasive synthetic route (Fig. 5.14a, Reaction C).…”
Section: Polymers Of Intrinsic Microporositymentioning
confidence: 97%